The SITE-100 Project: Site-Based Biodiversity Genomics for Species Discovery, Community Ecology, and a Global Tree-of-Life - Bian, Xueni; Garner, Beulah H.; Liu, Huaxi; Vogler, Alfried P. (Frontiers in Ecology and Evolution, 2022)
Most insect communities are composed of evolutionarily diverse lineages, but detailed phylogenetic analyses of whole communities are lacking, in particular in species-rich tropical faunas. Likewise, our knowledge of the Tree-of-Life to document evolutionary diversity of organisms remains highly incomplete and especially requires the inclusion of unstudied lineages from species-rich ecosystems. Here we present the SITE-100 program, which is an attempt at building the Tree-of-Life from whole-community sampling of high-biodiversity sites around the globe. Combining the local site-based sets into a global tree produces an increasingly comprehensive estimate of organismal phylogeny, while also re-tracing evolutionary history of lineages constituting the local community. Local sets are collected in bulk in standardized passive traps and imaged with large-scale high-resolution cameras, which is followed by a parataxonomy step for the preliminary separation of morphospecies and selection of specimens for phylogenetic analysis. Selected specimens are used for individual DNA extraction and sequencing, usually to sequence mitochondrial genomes. All remaining specimens are bulk extracted and subjected to metabarcoding. Phylogenetic analysis on the mitogenomes produces a reference tree to which short barcode sequences are added in a secondary analysis using phylogenetic placement methods or backbone constrained tree searches. However, the approach may be hampered because (1) mitogenomes are limited in phylogenetic informativeness, and (2) site-based sampling may produce poor taxon coverage which causes challenges for phylogenetic inference. To mitigate these problems, we first assemble nuclear shotgun data from taxonomically chosen lineages to resolve the base of the tree, and add site-based mitogenome and DNA barcode data in three hierarchical steps. We posit that site-based sampling, though not meeting the criterion of “taxon-completeness,” has great merits given preliminary studies showing representativeness and evenness of taxa sampled. We therefore argue in favor of site-based sampling as an unorthodox but logistically efficient way to construct large phylogenetic trees.